(untitled) (International journal of medical sciences, 2026)
The article examines the possibilities of teaching the Russian language in a medical university using intelligent digital technologies. Special attention is paid to the use of artificial intelligence elements for the formation of professional medical vocabulary and communicative skills of future doctors. Examples of using AI chatbots, interactive platforms, and digital simulators in the educational process are analyzed. The pedagogical effectiveness of intelligent digital technologies as a means of increasing motivation and improving the quality of language training of medical students is substantiated.